Tumor-derived microparticles promote the progression of triple-negative breast cancer via PD-L1-associated immune suppression. (28th December 2021) - Li, Cong; Qiu, Shi; Jin, Kun; Zheng, Xiaonan; Zhou, Xianghong; Jin, Di; Xu, Binghe; Jin, Xun
Abstract: Membrane vesicles, including exosomes and microparticles (MPs), serve to package and transfer the cellular cargo during inter/extracellular communication, which is of great interest in cancer development, especially in the dissemination of signal transduction-associated traits from donor cells to recipient cells. Although increasing evidence suggests that microparticles (MPs) contribute to the development of cancer, their unique characteristics remain to be exploited. Here, we examined the secretion of MPs in tumor tissues from triple-negative breast cancer (TNBC) patients and found that the tumor cells could release MPs loaded with immune checkpoint molecular programmed cell death ligand 1 (PD-L1), especially in patients treated with traditional clinical interventions, such as chemotherapy and radiotherapy. These PD-L1-loading MPs contribute to the suppressive immune microenvironment, eventually resulting in the tumor progression in TNBC. Mechanically, we proved that PD-L1-loading MPs could suppress the activation and function of functional cluster of differentiation CD8 + T cells. Meanwhile, the PD-L1-loading MPs could mediate the differentiation of macrophages toward the immune-suppressive M2 phenotype via the activation of the TANK-binding kinase 1 (TBK1)/signal transducer and activator of transcription 6 (STAT6) signal and suppression of the serine-threonine kinase (AKT)/mammalian target of rapamycin (mTOR) signal. Given the increasing MP production induced by traditional clinical interventions, we further combined chemotherapy with the PD-L1 inhibitor atezolizumab (ATZ) to efficiently abrogate the immunosuppression caused by the PD-L1-loading MPs. Therefore, our study unveils the mechanism by which tumor cells systemically evade immune surveillance by releasing the PD-L1-loading MPs, and provides new insights into clinical TNBC immunotherapy. Graphical abstract: Image 1 Highlights: Tumor cells release PD-L1 loading microparticles, instead of exosomes, to mediate immunosuppression in TNBC. Clinical interventions promote release of MPs from tumor cells, resulting in the immunosuppression in TNBC. PD-L1 loading MPs suppress CD8 + T cells activation and facilitate the differentiation of macrophages toward M2 phenotype. MPs promote M2 macrophages polarization through cGAS/STING dependent TBK1/STAT6 and AKT/mTOR signals simultaneously.